KETIDAKBERDAYAAN PEMILIK SAWAH DAN KETIDAKADILAN TERHADAP MEREKA: Kasus Penanaman Tembakau di Klaten - Faturochman Faturochman; Bimo Walgito (Populasi, 2002)
Owners of rice fields in this research express their powerlessness/helplessness when their property is used by another party. This is so because right from the very beginning the government has been treating them unfairly. Such injustice/unfairness is manifested in the procedure, distribution, and the relationship between rice field owners and the government, especially PTPN. From the perspective of procedure, injustice arises from denying rice field owners the opportunity to become actively involved in the cooperation arrangement with the user of their fields (PTPN). From the perspective of distribution, the income of when the rice fields are operated by PTPN is generally lower than that obtained when the field owners operate them. From the vantage point of relationship, the feeling of injustice arises from the existence of a large social gap between the two parties. This research has emphasized on the farmers’ point of view. Nonetheless, results from other studies conducted in the same area, whether on the underlying public policy or history, came up with similar conclusions.